2021
DOI: 10.1021/acsanm.1c03102
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Nanoparticle-Immobilized Porous Carbon Nanofibers for Nonenzymatic Dopamine Sensing

Abstract: Dopamine (DA) is a type of neurotransmitter that plays an important role in the functions of the central nervous system, as well as renal, hormonal, and cardiovascular systems. In particular, abnormal changes in dopamine concentrations could cause serious diseases such as sleeping and eating disorders, Parkinson’s disease, and addictive behaviors associated with drug abuse. However, it is difficult to detect the change in concentration level in a reliable manner when it is present in extremely small levels. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…Table 3 displays the anodic peak current (i pa ) 3, when compared to 3D C-IDRA, the results of shorter peak-to-peak (∆E p ) value recorded for 3D C-IDRA NF have proven that deposition of porous CNFs does improve the redox cycling process. Our research results regarding CNFs align with the findings of Kim and Lee [26] who similarly reported that the porous carbon structure leads to a significant augmentation in the active surface area for DA. Analyzing the ∆E p value of 3D C-IDRA NF, it produces a small value and does improve significantly the electron kinetic transfer of DA, compared to 3D C-IDRA.…”
Section: Effect Of Voltage Scan Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…Table 3 displays the anodic peak current (i pa ) 3, when compared to 3D C-IDRA, the results of shorter peak-to-peak (∆E p ) value recorded for 3D C-IDRA NF have proven that deposition of porous CNFs does improve the redox cycling process. Our research results regarding CNFs align with the findings of Kim and Lee [26] who similarly reported that the porous carbon structure leads to a significant augmentation in the active surface area for DA. Analyzing the ∆E p value of 3D C-IDRA NF, it produces a small value and does improve significantly the electron kinetic transfer of DA, compared to 3D C-IDRA.…”
Section: Effect Of Voltage Scan Ratesupporting
confidence: 91%
“…Besides, enzymatic-assay-based methods are not only costeffective but also have high sensitivity for DA [23,24]. Taking advantage of carbon nanofiber (CNF) [25], Kim and Lee introduced a ruthenium (Ru) nanoparticle-immobilized multiscale pore-containing carbon nanofiber-based field-effect transistor as a nonenzymatic sensor to detect DA [26]. Even in the presence of interfering biomolecules, the nonenzymatic sensor electrode recorded high sensitivity of DA concentrations as low as 1 fM.…”
Section: Introductionmentioning
confidence: 99%
“…A linear range of the sensor was ∼0.01–100 μM with a great sensitivity of 482.43 μA mM –1 cm –2 . Similarly, Kim et al employed Ru-MPCNF as a nonenzymatic sensor to detect DA and found that it had a high sensitivity of about 1.0 fM, even when interfering biomolecules were present. Due to the nonbiological operating mechanism, the manufactured sensor electrode also demonstrated a robust sensing capability with long lives.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the central nervous system, kidneys, cardiovascular system, and endocrine system [ 1 ]. DA levels can affect heart rate, leading to heart failure and Parkinson’s disease [ 2 ]. Therefore, in situ measurement of DA content can be obtained using biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, electrochemical monitoring of DA is an excellent strategy [ 3 ]. Lee et al [ 2 ] designed a ruthenium nanoparticle-immobilized multiscale pore-containing carbon nanofiber-based field-effect transistor nonenzymatic sensor to detect DA. They found that the porous carbon structure not only promoted the generation of small-size Ru particles, but also induced a large active surface area for DA.…”
Section: Introductionmentioning
confidence: 99%